Udder morphology and physicochemical structure of milk in Bafra (Chios x Karayaka) ewes - Seker, Ibrahim; Koseman, Abdurrahman; Kul, Selim; Kocyigit, Sezgin; Seker, Pinar (Univ Zulia, Facultad Ciencias Veterinarias, 2024)
It was aimed to determine the effects of udder type on udder traits, milk yield and some physicochemical properties of Bafra (Chios x Karayaka) ewes. The lactation length, daily milk yield, lactation milk yield, and daily average milk yield of ewes were determined. In addition the udder type were determined, udder and teat traits were measured. The fat, solid non-fat, protein, lactose, mineral, density, freezing point, and conductivity values of the milk were determined. Type 3 udder was observed at the highest rate (37.5%) and Type 5 udders were not detected in ewes. The lactation length, daily, and lactation milk yield values were calculated as 177.75 days, 868.60 g and 156.86 kg, respectively. Udder circumference, udder width, udder depth, right teat length, left teat length, right teat diameter, left teat diameter, the distance between teats and udder floor height from the ground was calculated as 40.95 +/- 0.63, 12.36 +/- 0.30, 16.24 +/- 0.40, 2.85 +/- 0.09, 2.76 +/- 0.09, 1.49 +/- 0.03, 1.43 +/- 0.04, 15.35 +/- 0.23, and 31.88 +/- 0.70 cm, respectively. Rates of fat, protein, lactose, solid non-fat, mineral and also density, freezing point, and conductivity were calculated at 5.17 +/- 0.30, 1039.08 +/- 0.31, 6.24 +/- 0.05, 11.51 +/- 0.10, 0.88 +/- 0.009, 1039.08 +/- 0.31 g center dot mL-1, -0.80 +/- 0.009 degrees C and 5.26 +/- 0.03 mS center dot cm-1, respectively. It has been determined that Bafra sheep can be a suitable breed for breeding in the conditions of Malatya, Province of Turkiye. However, more scientific research should be done on this topic and the level of milk production should be improved.
Tipo de ubre, características de la ubre y del pezón, y estructura fisicoquímica de la leche en ovejas Bafra (Chios × Karayaka)
Keywords: Bafra sheep; milk yield; physicochemical properties of milk; udder traits; udder type